Jati Kasilih Ku Janti As Cultural Communication Model In Organizational Leadership Succession At Tourism Village - Muslim Muslim; Andi Chairunnas; Ratih Siti Aminah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to examine how the Sundanese philosophical principle of Jati Kasilih ku Janti is implemented as a cultural communication model in organizational leadership succession at Pulo Geulis Tourism Village, Bogor City. The research addresses a theoretical gap in Indonesian cultural communication scholarship by systematically investigating how an indigenous Sundanese philosophy operationalizes as a functional and complete organizational communication system. Using a qualitative approach grounded in ethnography of communication methodology, data were collected through eight months of participatory observation (52 events), in-depth interviews with 23 informants across four organizational role categories, focus group discussions, and semiotic analysis of ritual objects and performative texts. Data analysis employed the interactive model of Miles, Huberman, and Saldana with source and method triangulation for validity. Findings reveal five philosophical value dimensions and three interlocking cultural communication patterns ritual communication (Serah Tampi), deliberative communication (Riungan), and symbolic communication each encoding distinct dimensions of the philosophy. The Regenerative Cycle Communication Model (RCCM) is proposed, comprising five components and three dynamic principles demonstrating that indigenous philosophy constitutes a complete and adaptive organizational communication system. This model contributes an empirically grounded, locally rooted theoretical framework to cultural communication scholarship and organizational communication theory in Indonesia.